Sacred space: nomadic experience (Journal of Philosophy Culture and Political Science, 2018)
The phenomenon of space as the most important category of nomadic culture has a special sacred character, as it expresses ideological motives, cultural norms and values. In this article, the task was set in order to reveal the sacredness of the category of space in the life of nomads, which is the quintessence of their spiritual world. The space- in this study is viewed as a category that is expressed in real facts having a value. Space is a category that is discussed in almost every methodological study but still represents a problem towards the real world. The specificity of the mythological space is the specificity of mythology in general as an early stage in the development of human consciousness. The basis of cosmological mythology is the description of the main parameter of the universe – space – as the basic condition for the existence of human life. Therefore, in this article, an attempt is made to interpret the cosmos model which is an instrument for understanding the culture of nomads andin particular, the phenomenon of space. Representation of space at nomads has special reservoir as in its religious, ecological, cultural, economic specifics of the relevant cultural standards and values. The space belongs to two characteristics of physical and spiritual lives of the person, and the set of space phenomena.Key words: sacred space, model of the universe, shanyrak, threshold.